2010
DOI: 10.1007/s12349-010-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of Melissa officinalis L. leaf extract in the treatment of volunteers suffering from mild-to-moderate anxiety disorders and sleep disturbances

Abstract: Botanicals are an alternative option to prescription drugs for the alleviation of symptoms due to anxiety disorders and insomnia. Melissa officinalis L. has been shown as an anti-stress and anxiolytic agent. We previously reported moderate stress improvement in mice in which Cyracos®, a standardized Melissa officinalis L. extract, was administrated. Cyracos® contains phytochemicals that inhibit gamma-aminobutyric acid catabolism. This was a prospective, open-label, 15-day study to evaluate the efficacy of Cyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 37 publications
7
31
0
8
Order By: Relevance
“…It has been argued that "the GABAergic system is a logical and promising target for new strategies to prevent and treat anxiety and its associated symptoms, such as restlessness and insomnia. GABA activity is mediated through GABAA and GABAB receptor-dependent inhibition of the CNS, and GABA catabolism relies on GABA transaminase (GABA-T) levels" (34). In addition, in our study no side effect was observed regarding taking M. officinalis capsules, which in line with other studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It has been argued that "the GABAergic system is a logical and promising target for new strategies to prevent and treat anxiety and its associated symptoms, such as restlessness and insomnia. GABA activity is mediated through GABAA and GABAB receptor-dependent inhibition of the CNS, and GABA catabolism relies on GABA transaminase (GABA-T) levels" (34). In addition, in our study no side effect was observed regarding taking M. officinalis capsules, which in line with other studies.…”
Section: Discussionsupporting
confidence: 90%
“…In a study, Cases et al used M. officinalis L. leaf in treating volunteers with mild to moderate anxiety disorders and sleep disorders and reported that the anxiety manifestation and insomnia decreased from 18% to 42% and 95% of the samples had responded to treatment (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study applied the STAI before and after within the same group evaluated (placebo or experimental). RNAm gene expression of enzymes related to the production of GABA in the hippocampus increased, although salivary markers such as cortisol and urinary such as 8-hidroxideoxiganosina stress did not change [26].…”
Section: Discussionmentioning
confidence: 87%
“…Необ-ходимо выделить 3 фитотерапевтических агента, наи-более исследованных и широко применямых в неврологии: валериану лекарственную (Valeriana officinalis L.), мяту перечную (Mentha piperita L.) и ме-лиссу лекарственную (Melissa officinalis L.) [9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: оригинальные исследованияunclassified